A Ten-Year Systematic Mapping of Cultural Aspects in Brazilian Digital Games - D’Martins, Gabriel Marra; Seabra, Rodrigo Duarte; Lima, Phyllipe (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Culture is recognized as a multifaceted reflection of a society’s ways of life, covering aspects ranging from dress and religious ceremonies to family structures and recreation. In this scenario, digital games have emerged as innovative platforms for documenting and expressing culture, acting as new repositories of collective memory in which cultural and historical meanings are preserved and shared, becoming an integral part of a community’s memorial heritage. Objective: This study investigates and analyzes Brazilian cultural preservation and diffusion in digital games developed in the country. Methodology or Steps: To investigate the integration of these aspects, we present a ten-year systematic mapping covering academic research published in national databases. The study started with an extensive search of scientific databases, identifying 1182 initial publications. After applying selection and exclusion criteria, the final dataset was narrowed down to 52 publications. Results: Most articles emphasize the language and expressions of both Brazilian indigenous peoples and in the teaching of Brazilian Sign Language and Portuguese, with many using Brazilian unique geography as a setting. In addition, social elements, such as Cangaço and the colonization process, are frequently explored. The study also revealed that although Role Playing Games show promise for immersive narratives in Brazilian culture, accessibility is still challenging, with many games unavailable to the public.